ANALISIS SIMPANG BERSINYAL : Studi Kasus : Persimpangan Jalan Kenjeran, Jalan Kedung Cowek, Jalan Raya Karang Asem, Kota Surabaya - Juliansyah, Daffa Alif; Moetriono, Hary (LPPM Universitas Bina Bangsa, 2023)
In this modern era, the increasing science and technology has led to increasing human activities followed by the growth of vehicle capacity and the decline in pedestrians. So the need for means of transport is inevitable. In the city of Surabaya, the need for transportation has become a primary need for the people of the city and the situation at the intersection of Kenjeran Street, Kedung Cowek Street, Karang Asem Highway, Surabaya City with intersection type 433 and 4 signal phases which is if one arm intersection is in the green phase, the other three phases are in the red phase. The method used in this study is the Indonesian Highway Capacity Manual Year 1997 (MKJI 1997). Researchers conducted a traffic survey of the number of vehicles passing for 3 days, namely Tuesday, Wednesday, and Thursday, it can be calculated the amount of traffic volume, intersection capacity, and the degree of saturation. From the results of the study, the highest traffic volume at the intersection of Kenjeran Street, Kedung Cowek Street, Karang Asem Highway, Surabaya City occurred on Tuesday at 17.00-18.00 WIB. Jalan Kenjeran (West) amounted to 849 pcu/hour, Jalan Kenjeran (East) amounted to 1175 pcu/hour, Jalan Kedung Cowek (North) amounted to 1806 pcu/hour and Jalan Karang Asem (South) amounted to 1665 pcu/hour. The results of the existing performance at the intersection of Kenjeran Street, Kedung Cowek Street, Karang Asem Highway, Surabaya City with intersection type 433 occurred on Tuesday at 17.00-18.00 WIB, having an average saturation level of 0.97